Vibration mechanism analysis for cylindrical roller bearings with single/multi defects and compound faults. (October 2020) - Cao, Hongrui; Su, Shuaiming; Jing, Xin; Li, Denghui
Highlights: A novel modeling method of cylindrical roller bearings with defects is proposed. Vibration mechanism of roller bearings with single/multi defects is revealed. The rotor unbalance affects the vibration response caused by inner raceway defects. Abstract: The generation of defects has a great influence on the vibration characteristic of roller bearings. Thus, it is very important to analyze the vibration mechanism of bearings with different kinds of defects by dynamic models which can make systematic descriptions of truly dynamic behavior. In this paper, dynamic models are developed based on the model proposed by Gupta to investigate the vibration mechanism of cylindrical roller bearings with localized defects. The inner raceway and rollers have five degrees of freedom (DOFs) in the model to better describe the complex dynamic behavior of bearings. Gyroscopic moment, centrifugal force and lubrication traction/slip between roller/raceway, roller/cage, cage/raceway are completely included. Moreover, modeling methods of single defect, multi-defects and compound faults are introduced with the consideration of additional deflection and the change of contact force direction caused by defects. The differential equations used to describe the motions of bearing components are solved by the fourth order Runge-Kutta-Fehlberg scheme with step-changing criterion. Vibration responses of bearings with single defect, multi-defects and compound faults are simulated by the models and analyzed in both time domain and frequency domain. Experiments have been carried out on bearing test rig. The validity of models built in the paper is proved by comparing the simulation results with experiments. In addition, fruitful vibration responses are discovered and proposed, which will provide strong theoretical supports for fault diagnosis of cylindrical roller bearings.